2015
DOI: 10.1007/s10393-015-1066-8
|View full text |Cite
|
Sign up to set email alerts
|

Landscape Utilisation, Animal Behaviour and Hendra Virus Risk

Abstract: Hendra virus causes sporadic fatal disease in horses and humans in eastern Australia. Pteropid bats (flying-foxes) are the natural host of the virus. The mode of flying-fox to horse transmission remains unclear, but oro-nasal contact with flying-fox urine, faeces or saliva is the most plausible. We used GPS data logger technology to explore the landscape utilisation of black flying-foxes and horses to gain new insight into equine exposure risk. Flying-fox foraging was repetitious, with individuals returning ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 35 publications
0
32
0
Order By: Relevance
“…For example, in Queensland, Australia, the habitat ranges of flying foxes have been overlapped with that of equines. This enhances the risk of cross-species transmission through the presence of infectious materials, such as urine and feces, in foraging areas utilized by both animals [9]. …”
mentioning
confidence: 99%
“…For example, in Queensland, Australia, the habitat ranges of flying foxes have been overlapped with that of equines. This enhances the risk of cross-species transmission through the presence of infectious materials, such as urine and feces, in foraging areas utilized by both animals [9]. …”
mentioning
confidence: 99%
“…Research has identified that while some areas have had more Hendra virus cases historically, given the flying-foxes’ spatiotemporal distribution across Australia, it is difficult to predict where cases might occur [27]. The possibility of direct transmission from flying-fox urine to horses also suggests that even small numbers of flying-foxes may dramatically increase the risk of an infection in horses [22, 24]. Therefore, it is important to address the uncertainty surrounding Hendra virus cases and ensure that all stakeholders are fully aware of the changing nature of flying-fox distribution, and consequently risk of infection with Hendra virus, over time and space.…”
Section: Discussionmentioning
confidence: 99%
“…Horses are thought to become infected via ingestion or inhalation of virus from pasture, water or surfaces contaminated with flying-fox excreta, with recent research suggesting that flying-fox urine is the most likely transmission medium [22]. Infection via direct contamination of mucous membranes may also occur [2224]. Of the seven human cases of Hendra virus infection, four (57%) have been fatal [21].…”
Section: Introductionmentioning
confidence: 99%
“…which hosts are potentially involved in transmission (key hosts)?/which species in the ecosystem are infected?epidemiological studies, such as seroprevalence, parasitological and/or molecular typing studies from humans and animals can be used to identify potential hosts.[70,81,9193]comparison of human and veterinary surveillance data can provide early indication that an outbreak of disease in humans may have a zoonotic origin.[94–96]2. is there potential for effective contact between host species and, if so, how do contact rates compare between versus within species?GPS tracking can be used to asses contact between wildlife species and between wildlife and domestic livestock.[94]ecological studies of wildlife hosts can identify potential interspecies transmission pathways to humans.[25]3. is there evidence of cross-species transmission and host shifts?population genomic and genetic studies can type infecting pathogen species and demonstrate gene flow across known host species.…”
Section: Disentangling and Quantifying Transmissionmentioning
confidence: 99%
“…Interhost species mixing patterns, particularly between animal populations, can be even more challenging to measure, although if largely dependent on spatial structuring can be inferred from degree of overlap in host ranges or habitats, as was done in a modelling study to identify key animal reservoirs of African trypanosomiasis [115]. Technological advances such as video-capture, radio-tracking and GPS tracking have also provided useful insights into wildlife population contact rates, both within species, for example, deer [127], and between species, such as in study on risk of Hendra virus transmission between flying-foxes and horses in Australia [94]. …”
Section: Disentangling and Quantifying Transmissionmentioning
confidence: 99%